Inreach: A Choreographic Process of Transversality - Foley, Jessica (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering. CTVR/The Telecommunications Research Centre, 2016)
This dissertation is based on artistic research practice and participant observation over a five year period (2010-15) with CTVR, the national telecommunications research centre in Ireland. CTVR's research focuses on future wireless, mobile and optical networks. It is spread over six academic institutions in Ireland (NUIM, UCC, DIT, DCU, UL and Tyndall), collaborating closely with technology companies to develop technology transfer and commercialisation, and is involved in European-wide projects as well as international collaborations. This research was catalyzed by CTVR's pragmatic and lyrical question: How do we Communicate Communications? posed in an effort to imagine its Education and Outreach program differently. By engaging with this question through artistic research and participant observation with CTVR the concept of inreach was developed by the author. inreach, imagined as a experimental counter-point to Education and Outreach, involved a durational process of devising and enacting a number of different experiments cooperatively with CTVR's researchers and staff. This thesis focuses upon two core experiments that were catalytic of transversality: Room 3.17 and Engineering Fictions. Tracing and describing the processes leading to the dialogic situations of the experiments and the learning developed through them makes up the body of the thesis. Various artistic research practices (including the author's) informed the process of inreach, as did the Author's practice of participant observation with CTVR. By writing through these experimental processes, reflexively and reflectively, a number of theories became legible in the practice: the educational theory of the hidden curriculum; the concept of transversality developed by Felix Guattari; and the history and philosophy of engineering as an occupation that matters politically in the world. These theories are brought together to form a theoretical distillery through which the experiments are subsequently thought and analysed in the thesis. Through the writing of the dissertation inreach becomes legible as a necessarily ongoing process that structures dialogic situations within the techno-scientific research context of CTVR. The gradual and contingent process of inreach becomes translated as a choreographic process of dialogue, making and listening supportive of communication in between occupations of artistic and engineering research. This thesis shows that inreach is a process both catalytic and supportive of transversality. It is a process that resists and struggles with argumentative dialectics of vertical authority and disrupts passive dialogics of horizontal habits and tendencies. Through a close reading of two inreach experiments, the thesis brings together a language of practice and theory that structures and narrates learning in this regard. This thesis both proposes and makes a claim for catalyzing, structuring, facilitating and supporting on-going experimental dialogic communication within techno-scientific academic-industrial research contexts. Overall, the thesis demonstrates that inreach is generative of experimental choreographic processes of transversality within CTVR, structured experimentally in between research occupations of art and engineering. Thus, the thesis offers insights on this process by addressing and narrating the complex challenge of communicating communications with CTVR.
Keywords: Electrical and Electronic Engineering, Ph.D.; Ph.D. Trinity College Dublin, 2016